2015
DOI: 10.3892/etm.2015.2654
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-cadherin in oral lichen planus

Abstract: Abstract. Oral lichen planus (OLP) is a common lesion of the oral mucosa that can progress to cancer. E-cadherin is involved in intercellular adherence and the pathogenesis, development and metastasis of tumors, and is considered to be an important indicator of tumor progression and prognosis. The aim of this study was to investigate the expression of E-cadherin in OLP in order to elucidate its role in the pathogenesis and malignant transformation of OLP and provide evidence to support the early diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…12 Downregulation of E-cadherin is considered as one of the hallmarks of EMT; meanwhile, mesenchymal molecular markers, such as vimentin and fibronectin, are up-regulated. 13,14 In the present study, we observed decreased E-cadherin and increased vimentin expression in basal region of OLP lesion, which is consists in previous study, 15 which first described the nature of the liquefaction degeneration in OLP is an EMT. Moreover, the epithelial cells undergoing EMT were prone to express CK19, b1 integrin, and nestin, sharing some characters of cancer stem cell, which was considered as the roots of cancer.…”
Section: Ifn-c Inhibits Viability Of Epithelial Cells But Induces Esupporting
confidence: 86%
“…12 Downregulation of E-cadherin is considered as one of the hallmarks of EMT; meanwhile, mesenchymal molecular markers, such as vimentin and fibronectin, are up-regulated. 13,14 In the present study, we observed decreased E-cadherin and increased vimentin expression in basal region of OLP lesion, which is consists in previous study, 15 which first described the nature of the liquefaction degeneration in OLP is an EMT. Moreover, the epithelial cells undergoing EMT were prone to express CK19, b1 integrin, and nestin, sharing some characters of cancer stem cell, which was considered as the roots of cancer.…”
Section: Ifn-c Inhibits Viability Of Epithelial Cells But Induces Esupporting
confidence: 86%
“…Thus, 51.9% of the OLP patients had an abnormal positive expression of E-cadherin compared to only 4.8% of healthy controls. Based on the results of various studies in which E-cadherin expression was associated with the development of malignancies, it has been suggested that E-cadherin may be a marker of malignant transformation of OLP [ 134 ]. Sridevi et al analyzed the expression of E-cadherin in several diseases of the oral cavity, oral submucosal fibrosis, oral leukoplakia, OLP, and OSCC.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of p16 ink4a promotes cell growth and often contributes to malignant transformation (Kato et al, 2006). Although E‐cadherin hypermethylation in OLP not been demonstrated so far, aberrant immunohistochemical staining of E‐cadherin was reported (Du & Li, 2015). Loss of membrane expression and decreased expression levels of E‐cadherin were observed in OLP (Sridevi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation results in the downregulated expression of the gene. We believe that hypermethylation may cause the aberrant expression of E‐cadherin, which has been linked to malignancy in OLP (Du & Li, 2015). Thus, the involvement of aberrant E‐cadherin expression in the pathogenesis of OLP should not be ruled out.…”
Section: Discussionmentioning
confidence: 99%